2017
DOI: 10.14417/ap.1287
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação breve da psicossintomatologia: Análise fatorial confirmatória da versão portuguesa do Brief Symptom Inventory 18 (BSI 18)

Abstract: O Brief Symptom Inventory 18 (BSI 18), originalmente desenvolvido por Derogatis em 2001, constitui um instrumento de rastreio do distress psicológico aplicável a populações comunitárias e clínicas. Os respondentes devem avaliar a intensidade (de 0 -Nada a 4 -Extremamente) com que, nos últimos sete dias, experienciaram dezoito manifestações de psicossintomatologia. Este trabalho pretendeu avaliar o comportamento psicométrico da versão portuguesa do BSI 18, procedendo ao estudo da sua estrutura fatorial, validad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Mental Health Symptoms. This study utilized the Portuguese version of the Brief Symptom Inventory-18 (BSI-18) [ 40 ] to measure participants’ mental health symptoms. The BSI-18 is comprised of 18 items that evaluate the psycho symptomatology experienced by individuals, using three subscales that examine somatization, depression and anxiety symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Mental Health Symptoms. This study utilized the Portuguese version of the Brief Symptom Inventory-18 (BSI-18) [ 40 ] to measure participants’ mental health symptoms. The BSI-18 is comprised of 18 items that evaluate the psycho symptomatology experienced by individuals, using three subscales that examine somatization, depression and anxiety symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Mental Health Symptoms (Depression and Anxiety). Participants’ perceived mental health symptoms (MHS) were measured using the anxiety and depression sub-scales of the Portuguese version of the Brief Symptom Inventory (BSI-18) [ 37 , 38 ]. The BSI-18 is an 18-item scale that measures depression, anxiety, and somatic symptoms in non-clinical populations and is helpful to screen MHS.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 describes the mental health symptom results, which indicated that study participants presented higher levels of somatization, depression, and anxiety symptoms than the general population, but lower levels of symptomatology than the clinical population. The study obtained the validation scores for the general population, encompassing people without mental health disorders, from the relevant literature [25], while acquiring the validation scores for people with mental health disorders from clinical/psychiatric samples. Regarding sexual functioning, Table 1 shows that participants also demonstrated lower levels of sexual functioning in comparison with the general population, using validation scores for healthy men from the general population.…”
Section: Resultsmentioning
confidence: 99%
“…The current research measured mental health using the Portuguese version of the Brief Symptom Inventory-18 (BSI-18) [25], which is comprised of 18 items and three subscales, encompassing somatization, depression, and anxiety. The depression subscale focuses on depressive disorders' core symptoms, which include dysphoric mood states and anhedonia, among others.…”
Section: Measurement Instrumentsmentioning
confidence: 99%